Life activities and nursing diagnoses of the street population. - Moreira Ximenes, Maria Aline; da Silva Gomes, Josiane; Leandro Cavalcante, Francisco Marcelo; Galindo Neto, Nelson Miguel; Áfio Caetano, Joselany; Moreira Barros, Lívia (UERJ Nursing Journal / Revista Enfermagem UERJ, 2021)
Objective: to evaluate performance of activities of daily living (ADLs) and to identify nursing diagnoses for people living on the streets. Methods: in this cross-sectional study of 52 people, data were collected between April and July 2017 using an instrument based on the Roper-Logan-Tierney theoretical model. ADLs with frequency of 40% or more were considered to be care-dependent; diagnoses were inferred using a Risner framework. Results: dependent ADLs were: working and playing (92.3%), dying (88.5%), expressing sexuality (76.9%), sleeping (71.2%), maintaining a safe environment (71.2 %), breathing (61.5%), eliminating body wastes (53.8%), and eating (51.9%). The most frequent diagnoses were: improved communication disposition (96%), ineffective airway clearance (94%), contamination risk (77%), and ineffective impulse control (73%). Conclusion: people living on the streets were found to be dependent on care in physiological, social and emotional ADLs.